Dental care and challenges for children with Down syndrome - Alyahya, Faisal Abdullah; Alfareh, Ali Mohammed; Albadr, Riyadh Mohammed; Jowher, Asaad Abdulhadi Al; Aljuaid, Fahad Khaled; Almutairi, Yousef Saleh; Bakrman, Hani Abdullah; Jafel, Abdulmohsen Saad; Alhamoud, Haifa Ahmed; Alsefri, Mohammed Faraj (International Journal Of Community Medicine And Public Health, 2022)
Children who have Down syndrome, a common genetic defect, are among the special needs children who are more likely to have poor dental health. These oral health issues may be caused by a variety of causes, including variations in oral morphological characteristics, malocclusions, restricted salivary flow, caries-promoting foods and pharmaceuticals, bruxism, and immunologic elements. Noncooperative disposition during dental treatment combined with comorbidities, poor dental health, and predisposition to periodontopathies puts people with Down syndrome at an elevated risk for lasting poor dental outcomes including dental extraction and infectious diseases, and other costly restorative therapy under general anesthesia which may introduce more health risks due to comorbidities. Accessing dental care from a qualified practitioner is often challenging for children with Down syndrome. In addition to hampering the provision of professional dental care for this demographic, behavior problems also impede the incorporation of preventive dental care measures in the home. Acquiring a dentist who is capable and disposed to serving children with Down syndrome can be difficult. Administration of necessary medical services among medical professionals may be impacted by perceptions toward Down syndrome, a lack of awareness concerning disabilities, and a stereotypical view of children with Down syndrome. Dental professionals must make sure that patients with Down syndrome receive regular, cost-effective dental care and that they are ensured every opportunity to improve their oral health-related quality of life.